Case study -- reducing mycotoxins in Brazilian crops: food safety in food security and food trade - Salay, Elisabete (International Food Policy Research Institute, 2003)
Mycotoxins are toxic chemical compounds produced by molds, which can have important consequences in human and animal health... The economic consequences of the presence of mycotoxins in food, feed, and agricultural crops can be severe. In fact, mycotoxins jeopardize the safety and availability of the food supply in many countries... Both the public and private sectors in Brazil are making a concerted effort to control mycotoxins in foods consumed by both humans and animals. -- from Text